Study on Flood Control Dispatching Rehearsal in Shenzhen River Basin - LENG Yubo; LIU Xunping; LIU Chuan (Renmin Zhujiang)
At present,it is difficult to carry out large-scale flood control project construction in Shenzhen River Basin.Therefore,to ensure the flood control safety of Shenzhen Reservoir and downstream Shenzhen River,this paper follows the requirements of the forecast,early warning,rehearsal,and preplan proposed by the Ministry of Water Resources for flood and drought disaster prevention and analyzes constraints to be considered when constructing the rehearsal scene.In addition,the joint flood control dispatching rehearsal is carried out in Shenzhen Reservoir and Shenzhen River.By simulating the influence of reservoir flood discharge on river channel level under typical conditions,the paper explores the potential of the reservoir in flood regulation and detention and discusses the feasibility of flood discharge by staggering the tide.The results show that Shenzhen River Basin faces the heaviest rainfall in a decade,and the local heaviest rainfall in Shenzhen Reservoir is no more than once in 100 years.At the same time,under the unfavorable conditions of astronomical tides,Shenzhen Reservoir can effectively regulate flood peaks and ensure the safety of flood control.The results reveal the optimal effect of reservoir dispatching on flood control safety of Shenzhen Reservoir and Shenzhen River,and the joint dispatching rehearsal of Shenzhen River and Shenzhen Reservoir can be realized scientifically and reasonably through the flood model.